Survival in patients with hypoechoic muscularis propria lesions suggestive of gastrointestinal stromal tumors in gastric wall - (:unkn) unknown (UNIV CATHOLIQUE LOUVAIN-UCL, 2015)
Background : Subepithelial lesions (SEL) on upper gastrointestinal endoscopy are frequently encountered and referred to endoscopic ultrasound (EUS). Management of small gastric hypoechoic SELs of muscularis propria (MP) is controversial since EUS-assisted fine needle aspiration may be inconclusive, and surgical excision may be too invasive. We aimed to analyze our gastric MP-SELs in terms of survival and confounding factors. Methods : Data from gastric hypoechoic MP-SELs suggestive of gastrointestinal stromal tumor (GIST) by EUS were retrospectively reviewed. Surgically resected GISTs were stratified according to the current pathological risk criteria. Results : Sixty-one patients were identified. The mean age was 55.5 +/- 13.2 years and 45.6% were male. Mean follow-up duration was 53.4 +/- 26.7 (12-110) months. Twenty-eight (45.9%) patients were managed conservatively (diameter 15.3 +/- 10.1 mm). There were no metastasis-or tumor-related deaths and no significant size changes (>= 5 mm) in this group during follow-up. Thirty-three (54.1%) patients underwent complete resection (diameter 34.2 +/- 14.1 mm) among which 25 (75.8%) had the final diagnosis of GIST; 2 (8.0%), 14 (56%) and 6 (24%) patients were classified in no-risk, very-low-risk, low-risk categories respectively, while 2 (8.0%) were in moderate-risk and only 1 (4.0%) was in high-risk category. Conclusions : The excellent survival of patients with small hypoechoic gastric MP-SELs with conservative management represents indolent course of those lesions. We suggest re-consideration of the recommendations in the current guidelines towards extending the follow-up intervals for small MP-SELs.
Keywords: survival; GIST; hypoechoic muscularis propria lesion; surveillance; surgery; CLINICAL-PRACTICE GUIDELINES; PROGNOSTIC-FACTORS; DIAGNOSIS; MANAGEMENT; OUTCOMES; GIST